Peningkatan Kemandirian Siswa Melalui Problem Based Learning pada Materi Liturgia Kelas XI SMKN 1 Ngabang - Susanti Susanti; Hartutik Hartutik; Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study is based on the problems faced by Grade XI students at SMKN 1 Ngabang, namely the lack of motivation for independent learning, which often leads to a less conducive classroom environment. Additionally, teachers have not yet implemented student-centered learning models in the teaching process. The aim of this study is to determine the improvement in students' independence and learning achievement through the application of the Problem Based Learning (PBL) model in the pastoral work material of the Church in the field of Liturgia. This classroom action research (CAR) was conducted in two cycles consisting of four stages: planning, implementation, evaluation, and reflection. The research subjects were 30 Grade XI students. Data were analyzed descriptively by comparing results between cycles. The focus of this study was on the dimension of independence, one of the profiles of Pancasila students, in order to enhance the affective aspect of learning. The results showed a significant improvement in students' independence, from 68% in the first cycle to 88% in the second cycle. In terms of cognitive aspects, students were categorized as advanced (30%), proficient (50%), and basic (20%). The improvement in learning outcomes between the first and second cycles indicates that the PBL model is effective in enhancing students' independence and academic performance. Reflections from this study recommend the need for continued support of students’ affective development to further strengthen their independent learning. In conclusion, the Problem Based Learning approach, when focused on the dimension of independence, has been proven to improve student learning outcomes in Grade XI.